Implementasi Manajemen Bank Sampah IT pada Komunitas Bank Sampah berbasis Masyarakat, Pemuda, dan Sekolah di Kabupaten Pasuruan - Amang Fathurrohman; M. Dayat; Zainul Ahwan; M. Daimul Abror; Lukman Hakim; Syukur Sugeng Apriwiyanto; Imam Syafi’i; Fafit Rahmat Aji; Mulyono Wobisono (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
Waste is still a problem in Indonesia. Because of waste, especially organic waste, contributes greatly to climate change due to greenhouse gases. In the management of waste that is generally open damping, particularly in Pasuruan, until now is still a problem that has not been unsolved. Therefore, the author will be presented in the study of implementation of integrated waste management based on IT and obstacles faced during the mentoring process. This mentoring activity was carried out at four Waste Banks based on community, schools, and youth in Pasuruan Regency with Community-Based Research (CBR) approach. The results showed that the various activities of Waste Bank application management mentoring based on IT gained widespread acceptance and appreciation from the Manager of Waste Bank in Pasuruan Regency. However, in the process of transition from Waste Bank management from manual-based until there was a change by utilizing IT required a process, time as well as the willingness of Waste Bank Manager, so that these applications could be fully utilized. In addition, the different types of community and management differences developed in Waste Bank also affected in the utilization of this Waste Bank Application to be applied continuously in their community.